Biofuel Cell Based on Carbon Fiber Electrodes Functionalized with Graphene Nanosheets. (6th April 2016) - Koushanpour, Ashkan; Guz, Nataliia; Gamella, Maria; Katz, Evgeny
Abstract : Carbon fiber electrodes were electrochemically modified with graphene nanosheets in situ deposited in the 3D-structure, characterized by field emission scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman scattering methods. The graphene-modified electrodes were further functionalized with PQQ-dependent glucose dehydrogenase and laccase and used for assembling a biofuel cell operating in the presence of oxygen and glucose "fuel". The paper represents novel approach to the production of graphene-functionalized electrodes and their use in biofuel cells, potentially applicable in implantable bioelectronics devices.